Zakat for Asnafs’ business by Lembaga Zakat Selangor / Nurul Husna Haron … [et al.] - Haron, Nurul Husna; Hassan, Hazlina; Jasni, Nur Syuhada; Abdul Rahman, Rashidah (Universiti Teknologi MARA Cawangan Selangor, 2010)
Islam provides a beautiful way of life in maintaining proper socio-economy of the ummah through the implementation of zakat. In this paper, the zakat distribution by way of zakat for Asnafs’ Business is looked at from the efforts made by Lembaga Zakat Selangor (LZS). Various entrepreneurship programmes have been carried out by LZS and these activities are strengthened by the corroboration with the expert parties. Zakat distribution is able to help the Asnafs (beneficiaries) in surviving life so as to alleviate poverty from the Muslim society. This Islamic socio-economic justice will beautifully reach its circle when the successful Asnafs who received the Zakat for Asnafs’ Business are no longer in need of the zakat, and in turn contribute to the zakat for the other Asnafs who are still surviving.